An Investigation of Time-Dependent Deformation Characteristics of Soft Dredger Fill - Wanying Wang; Qingzi Luo; Bingxiang Yuan; Xiaoping Chen (Advances in Civil Engineering)
The creep characteristics of soft clays have been studied for decades. However, the lateral deformation of soils is not allowed during the commonly used one-dimensional consolidation tests, which cannot describe the real deformation features of soils in practice. On the other hand, the influence of drainage distance on the mechanical properties of soil is still controversial, classified as hypothesis A and hypothesis B. For a better understanding of deformation characteristics of soft clay, especially which in long-terms, a series of conventional oedometer tests as well as novel geometric confined consolidation tests was conducted on soft dredger fill. The results show that the secondary consolidation coefficient of the soil sample Cα would increase firstly, followed by a small decrease with the increase of consolidation pressure generally. Cα would decrease with the consolidation time and also be reduced by preloading. The strain at the completion of primary consolidation would increase with the drainage distance, but the Cα would be affected little. Both compression index Cc and Cα of soft clay would reduce after preconsolidation, in which two parameters show an approximate linear relationship. The creep coefficient of soft clay under the geometric confinement Cαε k is larger than that under the oedometer test Cαε. However, the trends of the relationship between the creep coefficient and loading are consistent regardless of the confinement conditions.